EFFECT OF DIFFERENT CRYOPROTECTIVE AGENTS ON SKIM MILK AND DIMITROPOULUS EXTENDER FOR STALLION SEMEN CRYOPRESERVATION - Arifiantini, R.I.; Purwantara, B.; Yusuf, T.I.; Sajuthi, D. (Diponegoro University, 2010)
s to assess different CPAs on stallion semen cryopreservation. Skim milk (SM) and Dimitropoulos(DV) were the extenders used in this study; each was added by glycerol (Gly), combination of ethyleneglycol-glycerol (EG+Gly) or dimethilformamide (DMF). Each semen sample was evaluated and dividedequally into six tubes; semen in the three tubes was diluted 1:1 with (SM), while in the remaining tubesthe semen was diluted 1:1 by DV. After being diluted, all tubes were centrifuged at 1006xg for 10minutes. The supernatan discarded, the pellet was rediluted by SM trehalosa or DV trehalose, and addedby G, EG+Gly, or DMF to reach the final sperm concentration of 200x106/ml. The extended semen wasindividually packed in 0.3 ml minitube, equilibrated at 4oC for 2 hours, frozen in liquid nitrogen vaporfor 10 minutes, and then was stored in liquid nitrogen container at -196 oC. After 24 hours, the semenwas thawed at 37 oC for 30 second. There were no significantly different (p>0.05) on the percentages ofmotile and viable sperm in SMT (21.7% and 43.4%, respectively) compared with those extended withDV T extender (26.9% and 50.8%, respectively). DMF demonstrated better results as CPA compared tothe others; and DVTDMF combination had the best protection during cryopreservation in this study.